Love Your Enemies Discipleship, Pacifism, and Just War Theory - Cahill, Lisa Sowle (Minneapolis Fortress Press, 1994)
Questions of pacifism and just war, which have preoccupied Christian thinkers from time to time over the past 1700 years, are given distinctive treatment in this book as it discusses biblical sources for the questions, builds on historical examples both
Keywords: Peace -- Religious aspects -- Christianity -- History of doctrines. War -- Religious aspects -- Christianity -- History of doctrines. Pacifism -- Religious aspects -- Christianity -- History of doctrines